2012
DOI: 10.1038/ejcn.2012.137
|View full text |Cite
|
Sign up to set email alerts
|

Associations between usual school lunch attendance and eating habits and sedentary behaviour in French children and adolescents

Abstract: A country of glorious food, of superb restaurants and Sunday meals, France today is plunged into anguish and confusion.Must we, from now on, sacrifice the gentle principle of pleasure to the all powerful precautionary principle?Rumours grumble, worried in the markets and behind supermarket trolleys: what can we still eat? At the same time, the major diseases linked to malnutrition have fortunately almost disappeared, succeeded now by an explosion in unbalanced diets and illnesses linked to excess, which show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Study findings also show that the presence of a school canteen is especially important in predicting at least weekly fast-food intake in girls. We were surprised by this result, as one would expect that the presence of canteens may encourage healthier food habits ( 49 , 52 ) ; however, many schools worldwide still struggle to achieve healthier food and nutrient standards despite policy improvements ( 62 , 63 ) . It would be beneficial in the future to examine school canteen offerings to assess nutritional quality and acceptability, or whether girls are bringing in food purchased elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study findings also show that the presence of a school canteen is especially important in predicting at least weekly fast-food intake in girls. We were surprised by this result, as one would expect that the presence of canteens may encourage healthier food habits ( 49 , 52 ) ; however, many schools worldwide still struggle to achieve healthier food and nutrient standards despite policy improvements ( 62 , 63 ) . It would be beneficial in the future to examine school canteen offerings to assess nutritional quality and acceptability, or whether girls are bringing in food purchased elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…We also considered behavioural correlates reflecting the school lunch context, such as the presence of a school canteen (48)(49)(50) , which may be associated with healthy eating (51,52) and minimize the likelihood of consuming lunch elsewhere. In Denmark, provision of school cafeterias is not considered the norm, necessitating that most children attending school bring lunch from home (53,54) .…”
Section: Covariatesmentioning
confidence: 99%
“…O'Hara found no impact regarding inequalities in eating habits, physical activity, sedentary behaviour or BMI and van Hook and Altman 77 found not effect inequalities in the change of BMI from fifth to eighth grade. Three studies (Demment et al, 58 Wills et al 80 and Dubuisson et al) 60 examined other aspects of the obesogenic environment. Demment et al 58 found that a better nutrition and physical activity environment of schools' increased the positive impact of high household income on BMI, though not the negative impact of low household income.…”
Section: Obesogenic Environmentmentioning
confidence: 99%
“…Wills et al 80 -the only qualitative study included in this review-reported that better eating habits of peers might mitigate the negative impact of low family socioeconomic position on adolescents eating habits. Finally, Dubuisson et al 60 examined the impact of school canteen attendance on inequalities in eating habits and sedentary behaviour in children as well as adolescents but found no moderation.…”
Section: Obesogenic Environmentmentioning
confidence: 99%
“…In response to the problem, the UK and American Governments encourage healthier lifestyle choices with policy on vending. The French Government has taken stronger action and banned vending in places such as schools (Phillips et al , 2003; ten Have et al , 2010; Terry‐McElrath et al , 2014; Chauliac and Hercberg, 2012; Capacci et al , 2012; Dubuisson et al , 2012; Martin et al , 2011).…”
Section: Introductionmentioning
confidence: 99%